Impact of workforce diversity on organizational performance of Nepalese insurance companies - Chhetri, Swastika Raya (Nepalese Journal of Management, 2024)
This study examines the impact of workforce diversity on the organizational performance of Nepalese insurance companies. Organizational performance is the dependent variable. The selected independent variables are age diversity, cultural diversity, education diversity, experience diversity, gender diversity and marital diversity. The primary source of data is used to assess the opinions of respondents regarding workforce diversity in Nepalese insurance companies. The study is based on primary data with 125 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and multiple regression models are estimated to test the significance and importance of workforce diversity on the organizational performance in Nepalese insurance companies.The study showed that age diversity has a positive impact on organizational performance. It indicates that age diversity in the workforce leads to increase in organizational performance. The result also revealed that education diversity has a positive impact on organizational performance. It indicates that education diversity in the organization leads to increase in organizational performance. Similarly, experience diversity has a positive impact on organizational performance. It indicates that experience diversity among the employees leads to an increase in organizational performance. Likewise, gender diversity has a positive impact on organizational performance. It indicates that the diverse gender in the organization leads to increase in organizational performance. Further, cultural diversity has a positive impact on organizational performance. It implies that workforce of diverse cultural background leads to increase in organizational performance. Moreover, martial diversity has a positive impact on organizational performance. It reveals that diverse marital status in the workforce leads to an increase organizational performance of Nepalese insurance companies. The regression also showed that the beta coefficients are positive for age diversity, cultural diversity, education diversity, experience diversity, gender diversity and marital diversity and are significant for all the independent variables at one percent level of significance.